Composite early strength agent, early strength grouting material and preparation method and application thereof
By using a composite early strength agent composed of triethanolamine, sulfate and nitrate in wind power grouting materials, the problems of low early strength, poor fluidity and insufficient later strength of ordinary silicate cement in wind power grouting materials are solved, and high-performance wind power grouting materials are achieved, reducing costs.
Patent Information
- Application Number
- CN202411916589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, the application of ordinary silicate cement in wind power grouting materials has problems such as low early strength, poor fluidity and insufficient later strength, which is difficult to meet the high performance requirements of wind power grouting materials.
A composite early strength agent is used, which consists of triethanolamine, sulfate and nitrate. By combining it with silicate cement, it promotes the hydration of silicate cement, thereby improving the early strength and fluidity of the grouting material without affecting the later strength.
The comprehensive improvement of the early strength, later strength and fluidity of ordinary silicate cement in wind power grouting materials has been achieved, reducing the cost of raw materials and meeting the high performance requirements of wind power grouting materials.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based building materials, and relates to a composite early strength agent, an early strength grouting material, and a preparation method and application thereof; in particular, to a composite early strength agent for silicate cement, a wind power grouting material, and a preparation method thereof. Background Art
[0002] Due to the rich wind energy reserves and the green and low-carbon nature of wind power generation, the scale of wind power generation is expanding day by day. Wind power grouting materials play a key role in connecting wind power towers and foundation bases, which can effectively reduce construction and installation errors and reduce fatigue damage of wind turbines. As one of the important materials for wind tunnel structures, it is also increasingly in demand. Wind power grouting materials are a high-performance cementitious material with fast hardening, early strength and high fluidity characteristics. They are generally composed of cement-based cementitious materials, high-strength aggregates, admixtures and other functional components.
[0003] At present, cement, the main component of cementitious materials in wind power grouting materials, is generally divided into the following three systems: (1) Portland cement system, which is widely used and has good durability, but requires the addition of early strength agents, expansion agents, etc. to make up for its long hardening and setting time, low early strength and large drying shrinkage. At present, in order to improve the strength of grouting materials, P·O 52.5 cement and P·Ⅱ 52.5 are generally used; (2) Sulphoaluminate cement and high-alumina cement, which have fast hardening, early strength and slight expansion, and need to be regulated by adding retarders, but the strength shrinks in the later stage and the cost is relatively high; (3) Compounding of Portland cement and sulphoaluminate mineral cement or high-alumina cement. Among the above three systems, sulphoaluminate mineral cement and high-alumina cement are relatively expensive. Although the cost of the commonly used 52.5 Portland cement has decreased, it is still much higher than the 42.5 Portland cement with the largest amount used in engineering construction.
[0004] Therefore, in order to achieve the need of low cost of the project, it is of great significance to study the early strength of ordinary Portland cement represented by Ordinary Silicon 42.5 Portland cement and ensure its fluidity so that it meets the high performance requirements of wind power grouting materials. Summary of the invention
[0005] As mentioned above, 42.5 silicate cement, which is the most widely used in engineering construction, has the advantage of low cost. It is ordinary silicate cement with medium strength. Generally, early strength agent is often added to improve the early strength of cement. However, for wind power grouting materials, it is necessary not only to ensure its early strength, but also to take into account other properties, such as fluidity, late strength, etc.
[0006] The present invention provides a composite early strength agent, an early strength grouting material, and a preparation method and application thereof, so as to solve the above-mentioned defects of ordinary Portland cement in the prior art and realize the application of ordinary Portland cement in wind power grouting material.
[0007] Specifically, in a first aspect, the present invention provides a composite early strength agent for silicate cement, which is composed of triethanolamine, sulfate and nitrate; The mass ratio of the triethanolamine to the sulfate is 1:(13-16); The mass ratio of the triethanolamine to the nitrate is 1:(3-7).
[0008] Although there are related technologies that use triethanolamine as an early strength agent, the price of triethanolamine is relatively high. The present invention must strictly control its usage on the basis of controlling costs. Studies have found that by using a very small amount of triethanolamine in combination with sulfate and nitrate, the hydration of silicate cement minerals can be promoted to improve the early strength of the grouting material, without a negative impact on the later strength, while reducing the aggregation and adhesion of powder particles, thereby improving the fluidity of the grouting material.
[0009] Among them, sulfate is relatively cheap, especially sodium sulfate, which is the main component of the composite early strength agent for silicate cement of the present invention. Experiments show that although the early strength of silicate cement can be improved to a certain extent by using triethanolamine and sulfate in combination, the effect is very limited. Only by adding a small amount of nitrate on this basis can the comprehensive improvement of the early strength, late strength and fluidity of silicate cement be achieved, and the cost will not be significantly increased.
[0010] In the present invention, the mass ratio of the triethanolamine to the sulfate is 1:(13-16), for example, it can be any value of 1:13, 1:14, 1:15 and 1:16 or a range of any values.
[0011] In the present invention, the mass ratio of the triethanolamine to the nitrate is 1:(3-7), for example, it can be any value of 1:3, 1:4, 1:5, 1:6 and 1:7 or a range of any values.
[0012] Further preferably, the composite early strength agent for Portland cement comprises triethanolamine, sulfate and nitrate in a mass ratio of 1:15:4.
[0013] According to the composite early strength agent for Portland cement provided by the present invention, the sulfate is sodium sulfate and / or aluminum sulfate; preferably sodium sulfate.
[0014] According to the composite early strength agent for Portland cement provided by the present invention, the nitrate is sodium nitrate and / or calcium nitrate.
[0015] In a second aspect, the present invention further provides an early strength grouting material, comprising silicate cement and the composite early strength agent for silicate cement as described above; The mass ratio of the composite early strength agent for silicate cement to the silicate cement is (0.21-0.22):(42-44).
[0016] The invention prepares a composite early strength agent for silicate cement with a specific composition in silicate cement, so that the obtained grouting material has good early strength, late strength and fluidity, and lower raw material cost.
[0017] The early strength grouting material provided by the present invention further includes recycled micro powder; The mass ratio of the regenerated micro powder to the silicate cement is (3-5): (42-44); Preferably, the specific surface area of the regenerated micropowder is ≥400m 2 / kg; the recycled micro powder is obtained by grinding discarded concrete grouting blocks.
[0018] The recycled micro powder used in the present invention is obtained by grinding discarded concrete grouting material blocks, which can promote the reaction generation of CSH gel and improve the compressive strength of the early strength grouting material without affecting the fluidity.
[0019] The early strength grouting material provided by the present invention further includes graded quartz sand; The mass ratio of the graded quartz sand to the silicate cement is (31-36): (42-44); Preferably, the graded quartz sand is obtained by mixing 20-40 mesh quartz sand, 40-70 mesh quartz sand and 70-90 mesh quartz sand in a mass ratio of 35-50:25-40:25-35; further preferably, the graded quartz sand is obtained by mixing 20-40 mesh quartz sand, 40-70 mesh quartz sand and 70-90 mesh quartz sand in a mass ratio of 4:3:3.
[0020] The present invention also makes the system compactly stacked by the proportion of cementitious materials and aggregates and the aggregate grading design, thereby improving the strength of the grouting material and maintaining good fluidity of the grouting material.
[0021] According to the early strength grouting material provided by the present invention, the silicate cement is P·I 42.5 cement and / or P·O42.5 cement.
[0022] The early strength grouting material provided by the present invention comprises, by weight: 42-44 parts of silicate cement, 3-5 parts of fly ash, 9-12 parts of silica fume, 3-5 parts of recycled micropowder, 31-36 parts of graded quartz sand, 1.2-1.9 parts of water reducer, 0.21-0.22 parts of composite early strength agent for silicate cement, 1.3-3 parts of composite expansion agent and 9-10 parts of water.
[0023] In the present invention, the silicate cement content of 42-44 parts can be, for example, any value among 42 parts, 43 parts and 44 parts, or a range consisting of any values.
[0024] The fly ash of 3-5 parts can be, for example, any value among 3 parts, 4 parts and 5 parts, or a range consisting of any values.
[0025] The silica fume content of 9 to 12 parts can be, for example, any value among 9 parts, 10 parts, 11 parts and 12 parts, or a range consisting of any values.
[0026] The regenerated fine powder is 3-5 parts, for example, it can be any value among 3 parts, 4 parts and 5 parts or a range consisting of any values.
[0027] The graded quartz sand 31-36 parts can be, for example, any value among 31 parts, 32 parts, 33 parts, 34 parts, 35 parts and 36 parts, or a range consisting of any values.
[0028] The water reducing agent is 1.2 to 1.9 parts, for example, it can be any value or a range consisting of 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts and 1.9 parts.
[0029] The composite early strength agent for silicate cement is 0.21-0.22 parts, for example, it can be any value between 0.21 parts and 0.22 parts or a range consisting of any values.
[0030] The composite expansion agent is 1.3 to 3 parts, for example, it can be any value or a range consisting of 1.3 parts, 1.5 parts, 1.7 parts, 1.9 parts, 2.1 parts, 2.3 parts, 2.5 parts, 2.7 parts, 2.9 parts and 3 parts.
[0031] According to the early strength grouting material provided by the present invention, the water reducer is a polycarboxylic acid high-efficiency water reducer liquid; further preferably, the water reduction rate of the water reducer is ≥35%.
[0032] According to the composite early strength agent for silicate cement provided by the present invention, the silica fume is 95 grade semi-densified silica fume.
[0033] According to the composite early strength agent for silicate cement provided by the present invention, the composite expansion agent is composed of an azo plastic expansion agent and a calcium oxide-calcium sulfoaluminate expansion agent; further preferably, the mass ratio of the azo plastic expansion agent to the calcium oxide-calcium sulfoaluminate expansion agent is 1:(100~200).
[0034] In the present invention, the mass ratio of the azo plastic expansion agent to the calcium oxide-calcium sulfoaluminate expansion agent is 1:(100-200), for example, it can be any value or a range of any value among 1:100, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, 1:180, 1:190 and 1:200.
[0035] In a third aspect, the present invention also provides a method for preparing the early strength grouting material as described above, comprising: Premixing the silicate cement composite early strength agent with water to obtain a premix; The premix is mixed with a dry mix comprising the silicate cement to obtain an early strength grout.
[0036] By adopting the above technical scheme, the composite early strength agent for silicate cement is mixed and stirred with water in advance, so that part of the composite early strength agent can be dissolved in water in advance, thereby improving its uniformity of distribution in the grouting material, allowing it to fully exert its chemical excitation effect and prevent the problem of strength reduction caused by its uneven dispersion.
[0037] Preferably, the preparation method of the early strength grouting material comprises the following steps: (1) Cement, fly ash, silica fume, recycled micro powder, graded quartz sand and composite expansion agent are stirred and mixed to prepare a dry mix; (2) Mix water, water reducing agent and silicate cement with a composite early strength agent to prepare a mixed liquid; (3) The dry mixture and the mixed liquid are stirred and mixed for 3 to 5 minutes to obtain the grouting material.
[0038] In a fourth aspect, the present invention further provides the use of the composite early strength agent for silicate cement as described above, or the early strength grouting material as described above, or the early strength grouting material prepared by the preparation method as described above, in wind power grouting materials.
[0039] The present invention provides a composite early strength agent, an early strength grouting material, and a preparation method and application thereof. By compounding a composite early strength agent for silicate cement with a specific composition in silicate cement, cement mineral hydration can be promoted to improve the early strength of the grouting material without negatively affecting the later strength, while reducing the aggregation and adhesion of powder particles, thereby improving the fluidity of the grouting material. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels. Specifically: The water reducing agent used in the embodiments of the present invention includes but is not limited to: the ultra-high performance concrete special water reducing agent produced by China Building Materials Zhongyanyi Technology Co., Ltd. and the UHPC60 water reducing agent produced by Xiamen Xingbang New Materials Co., Ltd.; the water reduction rate thereof is ≥35%.
[0042] The graded quartz sand used in the embodiment of the present invention is obtained by mixing 20-40 mesh quartz sand, 40-70 mesh quartz sand and 70-90 mesh quartz sand in a mass ratio of 4:3:3.
[0043] The azo plastic expansion agent used in the embodiment of the present invention includes but is not limited to: azodicarbonamide.
[0044] The calcium oxide-calcium sulfoaluminate expansion agent used in the embodiments of the present invention includes, but is not limited to, HSCA calcium oxide-calcium sulfoaluminate expansion agent produced by Tianjin Baoming Co., Ltd.
[0045] The regenerated micro powder used in the embodiment of the present invention is obtained by grinding waste concrete grouting blocks, and its specific surface area is ≥400m 2 / kg.
[0046] The silica fume used in the embodiment of the present invention is 95-grade semi-densified silica fume.
[0047] Example 1 This embodiment provides a low-cost early-strength wind power grouting material, comprising the following raw materials in parts by weight: P·I 42.5 cement 43 parts, fly ash 4.7 parts, silica fume 9.4 parts, recycled micro powder 3.6 parts, graded quartz sand 31.7 parts, water reducer 1.8 parts, composite early strength agent 0.21 parts, composite expansion agent 2.5 parts, water 9.1 parts.
[0048] Among them, the composite early strength agent is specifically triethanolamine, sodium sulfate and calcium nitrate, and the mass ratio of the three is: triethanolamine: sodium sulfate: calcium nitrate = 1:15:4.
[0049] The composite expansion agent specifically includes an azo plastic expansion agent and a calcium oxide-calcium sulfoaluminate expansion agent, and the mass ratio of the two is: azo plastic expansion agent: calcium oxide-calcium sulfoaluminate expansion agent = 1:200.
[0050] This embodiment also provides a method for preparing the above low-cost early-strength wind power grouting material as follows: 1) Mix cement, fly ash, silica fume, recycled micro powder, graded quartz sand and composite expansion agent to prepare a dry mix; 2) Stir and mix water, water reducing agent and composite early strength agent to prepare a mixed liquid; 3) The dry mixture and the mixed liquid are stirred and mixed for 5 minutes to obtain the grouting material.
[0051] Example 2 This embodiment provides a low-cost early-strength wind power grouting material, which is basically the same as Example 1, except that the composite early-strengthening agent is replaced by a mixture of triethanolamine, sodium sulfate, aluminum sulfate and calcium nitrate, and the mass ratio of the four is: triethanolamine: sodium sulfate: aluminum sulfate: calcium nitrate = 1:7.5:7.5:5.
[0052] Example 3 A low-cost early-strength wind power grouting material comprises the following raw materials in parts by weight: P·I 42.5 cement 43 parts, fly ash 2 parts, silica fume 11 parts, recycled micro powder 4 parts, graded quartz sand 31.7 parts, water reducer 1.8 parts, composite early strength agent 0.21 parts, composite expansion agent 2.5 parts, water 9.1 parts.
[0053] The composite early strength agent specifically comprises triethanolamine, sodium sulfate and calcium nitrate, and the mass ratio of the three is: triethanolamine: sodium sulfate: calcium nitrate = 1:13:4.
[0054] The composite expansion agent specifically includes an azo plastic expansion agent and a calcium oxide-calcium sulfoaluminate expansion agent, and the mass ratio of the two is: azo plastic expansion agent: calcium oxide-calcium sulfoaluminate expansion agent = 1:200.
[0055] This embodiment also provides a method for preparing the above low-cost early-strength wind power grouting material: the same as in Example 1.
[0056] Comparative Example 1 This comparative example provides a grouting material, which differs from Example 1 in that no composite early strength agent is added.
[0057] Comparative Example 2 This comparative example provides a grouting material, which differs from Example 1 in that the composite early strength agent is replaced by 0.21 parts of sodium sulfate.
[0058] Comparative Example 3 This comparative example provides a grouting material, which differs from Example 1 in that the ratio of graded quartz sand is replaced by 20-40 mesh quartz sand: 40-70 mesh quartz sand: 70-90 mesh quartz sand = 4:2:1. Comparative Example 4 This comparative example provides a grouting material, which differs from Example 1 in that no recycled micropowder is added.
[0059] Comparative Example 5 This comparative example provides a low-cost early-strength wind power grouting material, which is basically the same as Example 1, except that the mass of the composite early-strength agent is replaced by a mixture of triisopropanolamine, sodium sulfate and calcium nitrate, and the mass ratio of the three is: triisopropanolamine: sodium sulfate: calcium nitrate = 1:13:4.
[0060] Comparative Example 6 This comparative example provides a low-cost early-strength wind power grouting material, which is basically the same as Example 1, except that the mass of the composite early-strength agent is replaced by a mixture of triethanolamine, sodium sulfate and calcium nitrate, and the mass ratio of the three is: triethanolamine: sodium sulfate: calcium nitrate = 2:13:4.
[0061] Comparative Example 7 This comparative example provides a low-cost early-strength wind power grouting material, which is basically the same as Example 1, except that the mass of the composite early-strength agent is replaced by a mixture of triethanolamine, sodium sulfate and calcium nitrate, and the mass ratio of the three is: triethanolamine: sodium sulfate: calcium nitrate = 1:26:2.
[0062] Comparative Example 8 This comparative example provides a low-cost early-strength wind power grouting material, which is basically the same as Example 1, except that the mass of the composite early-strength agent is replaced by a mixture of triethanolamine, aluminum sulfate and calcium nitrate, and the mass ratio of the three is: triethanolamine: aluminum sulfate: calcium nitrate = 1:3:28.
[0063] The embodiments and comparative examples were tested according to GB / T 50448-2015 "Technical Specification for Application of Cement-based Grouting Materials", and the performance table of the tests is shown in Table 1.
[0064] Table 1
[0065] It can be seen from Table 1 that, compared with Comparative Example 1 in which no early strength agent is used and Comparative Example 2 in which sodium sulfate is used as an early strength agent, the initial fluidity and 30 min fluidity of Examples 1 to 3 using the composite early strength agent are improved to a certain extent, the 1d and 3d compressive strengths are greatly increased, and the later strength is not negatively affected.
[0066] Comparing the comparative example 3 with different quartz sand gradations and the embodiments 1 to 3, the graded quartz sand used in the embodiments can improve the compressive strength of the grouting material at all ages without much change in the fluidity of the grouting material.
[0067] Compared with Comparative Example 4 which does not use the recycled micropowder, the fluidity of Examples 1 to 3 is not affected, and the compressive strength at each age, especially the early compressive strength at 1d and 3d, is improved to a certain extent.
[0068] Comparative Examples 5 to 8 are compared with Example 1. In Comparative Example 5, triisopropanolamine is used instead of triethanolamine in the composite early strength agent, which has little effect on the compressive strength at each age, but significantly reduces the fluidity of the grouting material.
[0069] In Comparative Example 6, the proportion of triethanolamine in the composite early strength agent was increased, which had no obvious effect on fluidity, and slightly decreased the 1d compressive strength, while slightly increased the 3d and 28d compressive strengths, with small changes. In addition, the price of triethanolamine is relatively high, so increasing the proportion of triethanolamine is of little significance.
[0070] In Comparative Example 7, the proportion of sodium sulfate in the composite early strength agent is increased, which promotes the formation of calcium sulfate in the early stage of hydration, but also causes a poor structure of the cement paste, thereby slightly reducing the fluidity and reducing the compressive strength at all ages.
[0071] In Comparative Example 8, the proportion of calcium nitrate in the composite early strength agent is increased, which has little effect on fluidity. Calcium nitrate significantly improves the 1d compressive strength by promoting C3S hydration and clinker dissolution, but its high proportion reduces the 3d compressive strength.
[0072] Comprehensively compared, the composite early strength agent provided by the present invention takes into account fluidity, early and late compressive strength and raw material cost.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite early strength agent for silicate cement, characterized in that: Its composition is triethanolamine, sulfate and nitrate. The mass ratio of the triethanolamine to the sulfate is 1:(13-16); The mass ratio of the triethanolamine to the nitrate is 1:(3-7).
2. The composite early strength agent for silicate cement according to claim 1, characterized in that: The sulfate is sodium sulfate and / or aluminum sulfate; And / or, the nitrate is sodium nitrate and / or calcium nitrate.
3. An early strength grouting material comprising silicate cement, characterized in that: It also includes the composite early strength agent for silicate cement according to claim 1 or 2; The mass ratio of the composite early strength agent for silicate cement to the silicate cement is (0.21-0.22):(42-44).
4. The early strength grouting material according to claim 3, characterized in that: Also includes recycled micro powder; The mass ratio of the regenerated micro powder to the silicate cement is (3-5): (42-44); Preferably, the specific surface area of the regenerated micropowder is ≥400m 2 / kg.
5. The early strength grouting material according to claim 3 or 4, characterized in that: Also included is graded quartz sand; The mass ratio of the graded quartz sand to the silicate cement is (31-36): (42-44); Preferably, the graded quartz sand is obtained by mixing 20-40 mesh quartz sand, 40-70 mesh quartz sand and 70-90 mesh quartz sand in a mass ratio of 35-50:25-40:25-35.
6. The early strength grouting material according to any one of claims 3 to 5, characterized in that: The silicate cement is P·I 42.5 cement and / or P·O 42.5 cement.
7. The early strength grouting material according to any one of claims 3 to 6, characterized in that: Calculated by weight, it includes: 42-44 parts of Portland cement, 3-5 parts of fly ash, 9-12 parts of silica fume, 3-5 parts of recycled micropowder, 31-36 parts of graded quartz sand, 1.2-1.9 parts of water reducer, 0.21-0.22 parts of composite early strength agent for Portland cement, 1.3-3 parts of composite expansive agent and 9-10 parts of water.
8. The early strength grouting material according to claim 7, characterized in that: The water reducer is a polycarboxylic acid high-efficiency water reducer liquid; further preferably, the water reduction rate of the water reducer is ≥35%; And / or, the silica fume is 95-grade semi-densified silica fume; And / or, the composite expansion agent is composed of an azo plastic expansion agent and a calcium oxide-calcium sulfoaluminate expansion agent; further preferably, the mass ratio of the azo plastic expansion agent to the calcium oxide-calcium sulfoaluminate expansion agent is 1:(100-200).
9. The method for preparing the early strength grouting material according to any one of claims 3 to 8, characterized in that: include: Premixing the silicate cement composite early strength agent with water to obtain a premix; The premix is mixed with a dry mix comprising the silicate cement to obtain an early strength grout.
10. Use of the composite early strength agent for silicate cement according to claim 1 or 2, or the early strength grouting material according to any one of claims 3 to 8, or the early strength grouting material prepared by the preparation method according to claim 9 in wind power grouting materials.